Our Stories Have Never Been Told: Preliminary Thoughts on Black Lesbian Cultural Production as Historiography in The Watermelon Woman - Richardson, Matt (Black Camera, 2011)
Cheryl Dunye's 1996 film The Watermelon Woman earned a place in cinematic history as the first feature-length narrative film written and directed by an out black lesbian about black lesbians. This article examines how the film provides an important opportunity to mark the burgeoning genre of black queer documentary as a historiographical medium. The documentary film is a tool that highlights underexplored issues in black experience and provides a cultural site for imagining new possibilities for black lesbian subjectivity and creating innovative approaches to representing sexuality in black filmmaking.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Lesbian "Making-of" Documentaries and the Production of Lesbian Sex - Hankin, Kelly (The Velvet Light Trap, 2004)
The Velvet Light Trap 53 (2004) 26-39 On December 2, 2001, HBO began airing Project Greenlight, a twelve-part documentary series chronicling the production of a feature film by novice writer-director Pete Jones. With its spectacle of backroom dealings, unchecked egos, and human frailties, the television series capitalized on the contemporaneous success of like-minded "reality" programs such as Survivor and Temptation Island. Perhaps more closely, Project Greenlight also tapped into the current vogue for the "behind-the-scenes" and the "making-of" genres, represented by straight-to-video titles such as Star Trek-Deep Space Nine: Behind the Scenes (1993), Making of Jurassic Park (1995), and The Matrix Revisited (2001), television programs such as the Sundance Channel's Anatomy of a Scene, HBO's First Look, and MTV's Making the Video, and the proliferation of behind-the-scenes and making-of packaging on DVDs. A reflection of the growth of film-related ancillary products in the 1980s, the ever-expanding Hollywood ego, and the demands of a twenty-four-hour television cable market, the increased appearance of the making-of documentary format no doubt also reflects the renewed interest in amateur filmmaking promulgated by the age of desktop video. Perhaps as a manifestation of this interest, making-of documentaries have become increasingly more detailed in their coverage. Whereas the 1981 television special The Making of "Raiders of the Lost Ark" (Phillip Schuman) focuses mostly on the film's stunt work, special effects, location shoots, and set design, the recently released making-of documentary The Matrix Revisited focuses on script development, preproduction, production, postproduction, and exhibition, introducing viewers to costume designers, storyboard artists, and editors along the way. This attention to production detail can also be seen in Sundance's Anatomy of a Scene, which hones in on the construction, from music to costume to camera work, of a single scene. And certainly raising the bar on the level of detail included in the making-of genre is Project Greenlight, which is a "warts-and-all" look at film production, from squabbles over budgets to catering fiascos. Despite the making-of video's increased attention to the minutiae of filmmaking, one of the areas that remains outside the purview of most Hollywood making-of documentaries is the production of sex. Discussions about the cinematic logistics of creating a sex scene—how, when, and with what resources—are usually not featured in making-of documentaries. Of course, given our celebrity-driven culture, the question of sex vis-à-vis film production, particularly a Hollywood film production, is hardly absent from the publicity that surrounds a film. It is not uncommon to hear actresses or actors discussing what it was like to kiss another actor on the set. But these kinds of concerns are usually the province of entertainment magazines and television, not the province of ancillary related products such as the making-of video. While stories of roles requiring nudity or sex scenes abound on television shows such as Access Hollywood, Entertainment Tonight, and E! News Daily,these kinds of topics are less likely to appear in production-generated documentaries. Indeed, while the production of the provocative sex scene between Halle Berry and Billy Bob Thornton in Monster's Ball (Marc Forster, 2001) generated much discussion on television entertainment programs, talk shows, and newsmagazines, it was the film's prison execution sequence that was featured in the Sundance Channel's making-of special on the film. Given the lack of focus on sex scenes in most making-of documentaries, it is interesting to note that the two existing making-of documentaries for lesbian-made, lesbian-themed feature films—The Making of Bar Girls (1995) and Moments: The Making of Claire of the Moon (1992)—both heavily focus on the production of lesbian sex. Moreover, both lesbian making-of documentaries emphasize the cast's and the crew's sexual titillation over the creation of sexual sequences. In this essay I look at what this strategy reveals about the collective climate and concerns of lesbian feature filmmaking in the United States today.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Uplift Cinema: The Emergence of African American Film and the Possibility of Black Modernity - Field, Allyson Nadia (Duke University Press, 2015)
Allyson Nadia Field recovers the forgotten body of African American filmmaking from the 1910s which she calls uplift cinema. These films were part of the racial uplift project, which emphasized education, respectability, and self-sufficiency, and weren't only responses to racist representations of African Americans in other films.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Why It Matters that Black Men and Queer Women Invented Digital Remix Culture - Kosnik, Abigail De (JCMS: Journal of Cinema & Media Studies, 2019)
The article offers information related to the incention of digital remix culture by black men and queer women. It mentions about technique of extracting segments from existing recordings and using them to form the musical tracks of hiphop songs; and nonqueer and nonfemale people have participated heavily in fan production, digital sampling and gave rise to culture that has proliferated and thrived on the internet primarily through the creative labor of minority musical and fiction artists.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Memorias americoafricanas en el trabajo de artistas brasileñas contemporáneas - Sardelich, Maria Emilia; Cao, Marian López Fernandez (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
La memoria hace referencia a un conjunto de funciones psíquicas que permiten la actualización de imágenes de hechos pasados o que se representan como pasados. A diferencia de los estudios históricos, los de la memoria resaltan las subjetividades, amplían la discusión más allá del recuerdo y el olvido, y desplazan el debate hacia quien tiene el derecho a narrar su historia y aquellos que en ella se encuentran. Las inquietudes en torno a la memoria y sus lugares también se hacen visibles en el inquieto horizonte artístico, en el que pasados recientes y distantes se articulan en registros sobre diversas formas de traumas. Este artículo propone una reflexión sobre las relaciones entre arte y memoria a partir de la producción de dos artistas brasileñas contemporáneas: Rosana Paulino (São Paulo, 1968) y Aline Motta (Niterói, 1974). El análisis de esa producción se fundamenta en la interdisciplinaridad de los estudios de la memoria y destaca cómo la creación artística ofrece una posibilidad de resignificación individual y colectiva. Asimismo, conceptúa memorias americoafricanas como aquellas que emergen no solo en la memoria individual de las artistas presentadas en este artículo, sino también en la de muchas otras mujeres que se identifican con Americoáfrica como un sistema etnogeográfico de referencia. Son memorias americoafricanas porque se han gestado en la resistencia y creatividad contra la opresión, la humillación y la deshumanización, y que se insurgen contra la historia única proponiendo una revisión de la historiografía del país y del arte producido a partir de esos lugares. Memory refers to a set of psychic functions that allow the updating of images of past events or events that are represented as past. Unlike historical studies, memory studies highlight subjectivities, expand the discussion beyond memory and oblivion, and shift the debate towards who has the right to narrate their history and those who are in it. The concerns about memory and its places also become visible in the restless artistic horizon, in which recent and distant pasts are articulated in registers about various forms of trauma. This paper proposes a reflection on the relationship between art and memory based on the production of two contemporary Brazilian artists: Rosana Paulino (São Paulo, 1968) and Aline Motta (Niterói, 1974). The analysis of this production is based on the interdisciplinary nature of memory studies and highlights how artistic creation offers a possibility of individual and collective resignification. Likewise, it conceptualizes African-American memories as those that emerge not only in the individual memory of the artists presented in this article, but also in that of many other women who identify with Africa-America, as a reference ethnogeographic system. They are African-American memories because they have been born in resistance and creativity against oppression, humiliation and dehumanization, and because they insurrect against the unique history, proposing a review of the historiography of the country and the art produced out of those places.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."–(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé